3 - Middle-level Academics as Institutional Managers: A Study on Leadership and Organisational Change at a Ugandan University - Mwangu, Alex Ronald (Journal of Higher Education in Africa, 2022)
This study examines how academic middle managers, specifically department chairs at a Ugandan university, conceptualise their leadership roles, identify the necessary skills for effective leadership of the department and reflect upon and grow from their practice and past experience in department leadership. The study was carried out at a university that is transitioning from a community- owned to a state-run institution. Data was collected from eighteen department chairs who were purposively sampled from five faculties, one institute and one school, and from four senior managers of the university, using semi-structured interviews. The data was analysed using latent thematic analysis. The findings revealed that department chairs considered their major roles to be: ensuring high academic standards, creating academic programmes, contributing to the financial soundness of the university through developing marketable programmes, ensuring accountability, etc. Nonetheless, they struggled in their new leadership roles due to limited capacity-building and mentoring initiatives for leadership. This put extra strain on the departmental chairs and affected their ability to meet the expectations of the appointing authority.